SURVIVAL RATE OF CERVICAL CANCER PATIENTS IN PROF. DR. I.G.N.G. NGOERAH GENERAL HOSPITAL - Mahastya, I Wayan Cahya; Budiana, I Nyoman Gede; Mulyana, Ryan Saktika; Suwardewa, Tjokorda Gde Agung; Wijaya Surya, I Gede Ngurah Harry (E-Jurnal Medika Udayana; Vol 13 No 8 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i08.P17, 2024)
ABSTRACT   Cervical cancer is a type of cancer that develops in the cervix as a result of an infection with high-risk HPV. Cervical cancer patients have varying survival rates. This will be influenced by the patient's prognostic factors such as age, histopathological type, metastases, stage, tumor size, and treatment modalities. This research employs an analytical observational approach and utilizes a retrospective cohort research design. Survival rates will be measured using Kaplan Meier and log-rank based on prognostic factors. The research was carried out at RSUP Prof. Dr. I.G.N.G. Ngoerah, utilizing data from cervical cancer patients in the year 2021. The sample in this study was 245 samples. From 245 samples, 55 patients (22.4%) experienced events (died), 32 patients (13.1%) were uncensored (alive), and 158 patients (64.5%) were censored. The highest one-year survival rate based on prognostic factors was patients with age <40 years (78.8%), histopathological type of SCC (78.1%), no metastases (78.2%), patients with stage I (81%), tumor size < 2 cm (82.9%), and treatment modalities of chemotherapy, radiotherapy, and hysterectomy (90%). The results of the analysis based on the log rank test which reports only the incidence of metastasis factors show significant results on the one-year survival of cervical cancer patients. The overall one-year survival rate for cervical cancer patients is 77.6%. To determine the survival rate for cervical cancer patients over three and five years, further research is required.   Keywords: Cervical cancer, HPV, Kaplan-Meier, Log rank, and Survival rate.